2019
DOI: 10.1111/1750-3841.14637
|View full text |Cite
|
Sign up to set email alerts
|

Solanum muricatum Ameliorates the Symptoms of Osteogenesis Imperfecta In Vivo

Abstract: Pepino (Solanum muricatum), which is an evergreen plant native to South America, is well‐known for its effects in antioxidation, antidiabetic activity, anti‐inflammation, and antitumor activity. A previous study in our lab indicated that Solanum muricatum (SM) extract promoted osteogenic differentiation by upregulating Wnt and BMP signaling pathway in rat bone marrow stromal cells. The osteogenesis imperfecta (OI) mouse model was used in order to further discover the osteogenic properties of SM extract in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…PPAR-ɣ has been proposed to be a major decision factor in MSC lineage commitment by promoting adipogenesis from MSCs [47]. In parallel, Solanum muricatum extract promoted the osteogenic differentiation of MSCs, ameliorating thus the symptoms of osteogenesis imperfecta in a rat vivo model [48]. The combined administration of Ptychotis verticillata extract and MSCs may represent a new approach to enhance the therapeutic issue.…”
Section: Resultsmentioning
confidence: 99%
“…PPAR-ɣ has been proposed to be a major decision factor in MSC lineage commitment by promoting adipogenesis from MSCs [47]. In parallel, Solanum muricatum extract promoted the osteogenic differentiation of MSCs, ameliorating thus the symptoms of osteogenesis imperfecta in a rat vivo model [48]. The combined administration of Ptychotis verticillata extract and MSCs may represent a new approach to enhance the therapeutic issue.…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin is widely used for chronic bronchitis, and also has an adjuvant treatment effect on patients with coronary atherosclerotic heart disease, diabetes, and hypertension (Tamtaji et al, 2019). Our previous research has demonstrated that quercetin, extracted from Solanum muricatum , promoted the osteogenic differentiation of rat BMSCs and thus ameliorated the symptoms of osteogenesis imperfecta in vivo (Wang et al, 2017; Wang et al, 2019). However, the mechanisms underlying the regulatory function of quercetin in BMSCs are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The pepino fruit is usually eaten as fresh juicy fruit, although some cultivars are used in vegetable salads due to their higher acidity content and herbaceous flavour (Prohens et al, 2002). Different studies found that pepino displays antioxidant, antidiabetic, anti-inflammatory and antitumor properties (Hsu et al, 2011;Shathish and Guruvayoorappan, 2014;Sudha et al, 2011;Virani et al, 2020;Wang et al, 2019;Yue et al, 2019Yue et al, , 2020. One of the most interesting features of pepino is its close phylogenetic relationship with the major crops potato and tomato (Särkinen et al, 2013;Spooner et al, 1993).…”
Section: Introductionmentioning
confidence: 99%